2012
DOI: 10.1102/1470-7330.2012.0005
|View full text |Cite
|
Sign up to set email alerts
|

CT-based quantitative SPECT for the radionuclide 201Tl: experimental validation and a standardized uptake value for brain tumour patients

Abstract: We have previously reported on a method for reconstructing quantitative data from 99mTc single photon emission computed tomography (SPECT) images based on corrections derived from X-ray computed tomography, producing accurate results in both experimental and clinical studies. This has been extended for use with the radionuclide 201Tl. Accuracy was evaluated with experimental phantom studies, including corrections for partial volume effects where necessary. The quantitative technique was used to derive standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These results with 177 Lu are consistent with previous publications that have tested the accuracy of SPECT reconstructions using diagnostic imaging radionuclides such as 99m Tc, 123 I and 201 Tl [ 2 , 7 9 , 15 , 16 , 21 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results with 177 Lu are consistent with previous publications that have tested the accuracy of SPECT reconstructions using diagnostic imaging radionuclides such as 99m Tc, 123 I and 201 Tl [ 2 , 7 9 , 15 , 16 , 21 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…The methodology that we have developed and previously reported for quantitative SPECT [ 2 , 7 9 ] has been adapted for imaging the 177 Lu distribution in vivo, with appropriate modifications for the radionuclide. This uses the CT scan with conversion from Hounsfield units to attenuation coefficients for attenuation correction and for transmission-dependent scatter correction [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…To obtain a high level of standardization of scans with different camera systems and to reduce partial volume effects when evaluating small structures such as the pons, all scans were corrected for 1. Attenuation: Chang method [38] with automatically generated ellipses, and an attenuation coefficient μ of 0.146 has been used, the high value for μ corresponding to the "narrow beam attenuation coefficient" that is recommended when scatter correction is applied [39]. 2.…”
Section: Spect Imagingmentioning
confidence: 99%
“…Kathy Willowson et al, had proposed a method to improve and confirm a quantitative technique for SPECT, based on CT. This was done to find out the practicality of this method being imposed on SPECT images of brain tumor with a developing SUV . They concluded that their method is a very feasible method of quantifying the SPECT data.…”
Section: Hybrid Imaging Modalities In Actionmentioning
confidence: 99%